Synergistic anti-osteoporosis effects of Anemarrhena asphodeloides bunge–Phellodendron chinense C.K. Schneid herb pair via ferroptosis suppression in ovariectomized mice - Deng, Xuehui; Xiao, Wenlong; Lin, Bingfeng; Wang, Fang; Song, Li; Wang, Nani (Frontiers in Pharmacology, 2024)
Ferroptosis plays a crucial role in the progression of postmenopausal osteoporosis. Anemarrhena asphodeloides Bunge/Phellodendron chinense C.K. Schneid (AA/PC) is the core herb pair in traditional Chinese medicines formulae for postmenopausal osteoporosis treatment. However, the synergistic effects, and mechanisms, of AA/PC on alleviating ferroptosis and postmenopausal osteoporosis remain unclear. The goal herein was to analyze the effective ingredients and molecular mechanisms of AA/PC in the treatment of osteoporosis through serum pharmacochemistry, network pharmacology, metabolomics analysis, and pharmacodynamics evaluation. A bilateral ovariectomized (OVX) mouse model was established. Micron-scale computed tomography analysis showed that AA/PC increased bone mineral density in OVX mice. The effects of AA/PC were better than AA or PC alone on inhibiting the bone resorption marker nuclear factor of activated T-cells 1. Furthermore, five absorbable compounds were detected in serum: mangiferin, magnoflorine, berberine, timosaponin BIII, and timosaponin AIII. Network pharmacology showed these compounds had close relationship with seven ferroptosis targets. Importantly, compared with AA or PC alone, the AA/PC herb pair exerted better effects on regulating crucial ferroptosis pathways, including the system xc-/glutathione/glutathione peroxidase 4, transferrin receptor/ferritin, and acyl-CoA synthetase long chain family member 4/polyunsaturated fatty acids signaling pathways. These results indicate that AA/PC exerts synergistic effects on regulating glutathione synthesis, iron homeostasis, and lipid metabolism in ferroptosis. This work lays the foundation for further development and use of AA/PC herb pair for preventing and treating postmenopausal osteoporosis.